ARCHEOLOGY OF MOBILE BANKING IN AFRICA: THE IVORIAN MODEL IN FOCUS - Kamga, Osée (European Scientific Journal, ESJ, 2015)
The paper analyses how the initial form of mobile banking, which arose in the informal sector of the economy in Africa, triggered mobile phone transformation in the continent and contributed to the development of its mobile banking industry. Focussing on this specific marginal beginning of mobile banking in CÃ´te dâ€™Ivoire, the paper articulates how the principles it generated can inspire communication for development initiatives. However, there is also an attempt to suggest the concept of â€œproportional technologiesâ€ as a more productive theoretical framework to account for information and communication technology (ICT) practices in the developing world.